(untitled) (Journal of the College of Basic Education, 2022)
that the importance of the search is using quality exercises accompanying the devices to develop physical capacity and performance for golfers triple jump, laying the foundations for the correct scientific when using physical exercise and thus contributes to this research scientific contribution to serious consideration in the study of one of the problems in the field in the effectiveness of the tripartite jump.The research aims to: The preparation exercises using means of assisting the fit and capabilities of a sample of empirical research. The preparation of the training by means of various assistance to develop the physical abilities of the players of the tripartite jump. The imperatives of the search was as follows: There are differences with statistical significance between tribal tests and expost assessments in the physical abilities of a sample of empirical research. The use researcher experimental approach to one group already nature of the search for reasons related to the achievement of the objectives of the study and they are of the players of the specialized school Track and Field Athletics in the tripartite jump the (8) players, was achieving coherence in the variables (length and weight, and age, the age of the training program ), it took the curriculum ( 8 ) weeks and 2,112 three units in the week. The researcher reached the following conclusions:. Use of relevant exercises quick reactions have contributed to foment muscles, which contributed to the development of the physical abilities within the requirements of the effectiveness of the tripartite jump. The most important recommendations reached by the researcher are:. Use of exercises proposed quality under study in the minefield marking and eradication programs physical abilities and the development of the performance level of effectiveness of the tripartite jump.